THE FOUNDATION OF ISLAMIC EDUCATION MANAGEMENT DEVELOPMENT FROM KH M THOLHAH HASAN'S PERSPECTIVE - Nurdiyanti, Yanti; Masitoh, Imas; Nukhbatillah, IsyfiAgni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to explore the theological foundation to strengthen the philosophical impact on the strength of practical meaning so that it is not large but empty without a theological foundation as the foundation for the development of Islamic education. This research is a library research with the method used by literature study, using primary data sources from the works of KH M Tholhah Hasan and secondary data from other relevant works. Data analysis techniques using Miles and Hubbarman techniques. The results of the study state that the basic beliefs and philosophical views of KH M Tholhah Hasan which guide the development of Islamic education consist of; four basic beliefs and philosophical views, namely Islamic beliefs and views about God, humans, life and natural funds as well as philosophical views on; the concept of divinity, development of human nature, opportunities to develop themselves and opportunities to develop scientific studies. The foundation for the development of educational management consists of; theological foundation, philosophical foundation, sociological foundation, psychological foundation and scientific foundation. The foundation is used as a foothold in developing Islamic education with goals consisting of; macro goals as the main target, micro goals as practical targets and essential goals as ideal targets.